Effects of lamb sex, parity, and birth type on milk yield, lactation length, and milk components in Zom ewes raised under semi-intensive conditions - Bayril, T.; Akdemir, F.; Baran, M. S.; Orhan, C.; Yildirim, I. H.; Yildiz, A. S.; Celik, R. (South African Journal of Animal Sciences, 2023)
This study aimed to determine the effects of parity, birth type, and lamb sex on milk yield, lactation length, milking period, and milk components in Zom ewes. In this study, which included 83 Zom ewes, it was observed that birth type affected daily and lactation milk yield, and only parity affected lactation length. The effects of the milking period on milk yield and birth type on milk fat content were marked. The effect of lamb sex on protein, solid non-fat, and lactose contents was substantial, but that of parity and birth type were not statistically significant. There was a negative correlation between lamb sex and solid non-fat, protein, lactose, and density and between fat, protein, and lactose. There was a positive correlation between the fat and solid non-fat content, freezing point, and mineral content. In conclusion, the effect of milking period was statistically significant for milk yield and components. Additionally, the effects of lamb sex on solid non-fat, protein, and lactose contents were found to be substantial.
Keywords: lamb sex; milk components; milk yield; Zom ewes